Selective Adsorption of Dibenzothiophene Using Magnetic Molecularly Imprinted Polymers - Weihong Huang; Hui Li; Wanzhen Xu; Wei Zhou; Zhiping Zhou; Wenming Yang (Adsorption Science & Technology)
In this study, a novel and quick method for selective adsorption of dibenzothiophene (DBT) from gasoline using magnetic molecularly imprinted polymers (MMIPs) as the adsorbent has been employed. The MMIPs were prepared by a surface molecular imprinting technique, using Fe 3 O 4 magnetite nanoparticles as a magnetically susceptible component, DBT as template molecule, 4-vinylpyridine (4-VP) as functional monomer and ethylene glycol dimethacrylate (EGDMA) as cross-linker. The synthetic MMIPs were characterized by Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM) and vibrating sample magnetometer (VSM). The adsorption performances of MMIPs were investigated by batch adsorption experiments in terms of adsorption kinetics, isotherms and selective recognition. The results of the study indicated that MMIPs were able to adsorb DBT well, the adsorption equilibrium time was about 5 h and the equilibrium adsorption amount was 22.23 mg/g at 318 K. In the corresponding selectivity test, MMIPs exhibited a greater adsorption capacity towards DBT than the other three analogues.